A generic energy systems model for efficient ship design and operation. (May 2017) - Tillig, F; Ringsberg, JW; Mao, W; Ramne, B
There is an environmentally and economically motivated need to reduce the fuel consumption and air emissions of ships. To achieve a reduction in energy consumption, the energy flow in the entire energy system of a ship must be analysed in both the component, or subsystem, level as well as in a holistic way to capture the interactions between the components. Of the currently available energy consumption monitoring and prediction methods or models, no single model or method can be used to assess the energy efficiency of an arbitrary vessel in both the early design phase and during operation. This study presents a new generic ship energy systems model that can be used for this purpose. This new model has two parts: one for the assessment of a ship's energy consumption based on an ordinary static power prediction and one for advanced operational analysis, considering hydrodynamic and machinery systems effects. A Panamax tanker vessel was used as the case study vessel to prove the versatility of the model for five example simulations for the design and operation of ships. The examples include variations of the main dimensions, propeller design, engine layout and the operational profile on a North Atlantic route. From the results, different areas with a potential for energy savings were identified.